Teorema de Pitágoras, aplicações de demonstrações em sala de aula - Tartaglia Filho, Leonardo (2016)
[ENG]The official curriculum of the state of São Paulo in their spiral character, discusses the Pythagorean Theorem as one of their learning situations for the 9th year of elementary school, and on top of that content, contextualizes the topic in several other opportunities in high school, one of the most common theories in the Euclidean geometry. The work contributes in the creation of skills and competencies necessary for the understanding of geometry, which is apparent or not the figure of the right triangle, with the aim of providing tools for students to build knowledge necessary in order to find solutions to the problems posed by notebook student, which is the basic curriculum for all students of the state of São Paulo school. The activities, as workshops and activity sheets, proposed by the developer of this dissertation were applied to 35 students of the 9th grade of elementary school of the State School Pedro Bento Alves, located in central city of Arandu, state of São Paulo, which has in its framework students 800 students, divided shapeless way in 22 classrooms. Through the activity sheets, the author made the draft statements for the Pythagorean Theorem through manual labor, which believes it has a more significant effect to the students. The results were analyzed and compared with the assumptions previously raised during the preparation and creation of the dissertation, and the Didactic Engineering as the main research methodology and data analysis. Proposals classes had a good development because students behaved as protagonists of actions, being motivated and participative during the execution of activities. Students reached the proposed objectives, understanding that the material developed provided a different routine, as it has been applied, and thus conclude that the leaves of activities will be useful to all teachers who want to develop them in their classes, adapting -the as reality, performance and utilization of their students. The work contributed greatly to the professional development of the author, since rethink strategies and pursue new activities through research, raised the level of knowledge on the subject, which provided new practices in the classroom.